Antibacterial Potential Ethanol Extract of Papaya Leaves (Carica papaya Linn.) Towards Salmonella typhi - Mahatir Muhammad; Nasri Nasri; Vera Estefania Kaban; Denny Satria; Henni Cintya (Program Studi Pendidikan Biologi, 2022)
Infectious diseases are a problem of great concern throughout the world. Bacterial infections such as Salmonella typhi often attack children and cause diarrhea and typhoid fever. Salmonella typhi is a beflagellated Gram negative bacteria that can be transmitted through contaminated food, drink, or water. Treatment of infections using antibiotics, where often the use of antibiotics is not achieved on the therapeutic target due to lack of patient compliance in taking antibiotics, will cause new problems, namely problems related to antibiotic resistance. Papaya leaf is a plant originating from the Caricaceae family which, based on studies, has been reported to have antimicrobial, antidiabetic, and immunomodulatory effects. The purpose of this study was to examine the antibacterial potential of ethanol extract of papaya leaves (Carica papaya Linn.) against Salmonella typhi bacteria. This research method uses the agar diffusion method (Kirby-Bauer) with various concentrations to determine the minimum inhibitory concentration (MIC) and the streaking method to determine the minimum killing concentration (MBC). The minimum inhibitory concentration was obtained at a concentration of 3.125 mg/mL with an inhibitory zone diameter of 6.70 ± 0.20 mm and a minimum killing concentration of 50 mg/mL. The index activity value at a concentration of 300 mg/mL was 0.688 ± 0.05. So it can be concluded that the ethanol extract of papaya leaves has potential antibacterial activity against Salmonella typhi bacteria.